TITIK TEMU PEMAHAMAN ANTARA JIHAD DAN TERORISME - Mukhlishi, Mukhlishi (Universitas Islam Madura, 2015)
Lately Indonesian nation knocked over by crisis, both economics or moral crisis among others marked with existence of interpreted terrorism as fisabillah jihad, corruption which runs in all governance rule, and Drugs which not merely among student, society even have happened among all judges. Jihad and Terrorism is two matters which always have implication to discredit Islam in life of nation and state because it can break perfection of State and nation. Terrorism can bother stability of State and affect collectively. Its meaning is one who do not understand and keep off direct in problem which is being happened have to become victim. So that we can give information one another which can anticipate and get dubiously of real correct law.